2019
DOI: 10.1177/1473325019881226
|View full text |Cite
|
Sign up to set email alerts
|

Art as a transformative practice: A participatory action research project with trans* youth

Abstract: Given that promoting social justice is one of the central organizing principles of social work, it comes as no surprise that participatory action research (PAR) has gained much attention among social work researchers. While much has been written about promising practices of PAR with various marginalized communities, there remains a dearth of PAR literature that focuses on trans* people, a population often under attack in current socio-political climates. In this paper, we report on a PAR project in which a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…Youth also participated in the development of a unique graphic illustration. This is significant because previous research has identified arts-based research as a potential transformative (participatory) qualitative research process 36 …”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Youth also participated in the development of a unique graphic illustration. This is significant because previous research has identified arts-based research as a potential transformative (participatory) qualitative research process 36 …”
Section: Concluding Discussionmentioning
confidence: 99%
“…This is significant because previous research has identified arts-based research as a potential transformative (participatory) qualitative research process. 36 In this article we noted several challenges to the development and management of youth summits, which provide insight into how similar events could be improved in the future. Recruitment of youth is a time-consuming process, but we believe that it was vital to the success of the events.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…In accordance with Happell and Roper's (2007) consumer consultation approach to PPI, this study acknowledged the advisors' lived experience as expertise, consulting with the advisors for specific guidance throughout the research process. A lack of research involving TGDN community members, and the continuing experiences of marginalization faced by this community, justified the use of PPI methods in this research (Asakura et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…To date, research investigating TGDN health has largely been framed within a deficit model that emphasizes distress and dysfunction among TGDN people . As a result, the identity of TGDN individuals is embedded within discourses of mental illness (Asakura et al, 2019). The pathologising of TGDN identities through deficit-oriented research may inadvertently reinforce transphobic attitudes and fuel adverse health outcomes for TGDN individuals .…”
Section: The Current Studymentioning
confidence: 99%
“…In a course on curriculum inquiry, wherein students draft research designs, the new definitions also proved useful, informing a syllabus rife with examples of activist-oriented research. Such texts reinforced action research principles while highlighting relevant methodological skills: Upton's (2020) endorsement of decolonial, coconspiring approaches; Rademaker's (2021) conversation about feminist lenses; and vivid illustrations of critical data collection techniques (e.g., Asakura et al, 2020;Caraballo & Lyiscott, 2020). Discussing these texts with peers and applying pertinent insights to individual assignments, students demonstrated their capacity to connect their learning from content-focused courses to the not-soneutral methodological logistics of a DiP.…”
Section: Applicationsmentioning
confidence: 99%